1997
DOI: 10.2337/diab.46.5.750
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Is the Mode of β-Cell Death Responsible for the Development of IDDM in the Nonobese Diabetic (NOD) Mouse

Abstract: The NOD/Lt mouse, a widely used model of human autoimmune IDDM, was used to establish the mode of beta-cell death responsible for the development of IDDM. Apoptotic cells were present within the islets of Langerhans in hematoxylin and eosin-stained sections of pancreases harvested from 3- to 18-week-old female NOD/Lt mice (a range of 11-50 apoptotic cells per 100 islets). Immunohistochemical localization of insulin to the dying cells confirmed the beta-cell origin of the apoptosis. Although some islets from ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
85
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(87 citation statements)
references
References 0 publications
2
85
0
Order By: Relevance
“…These results are in agreement with studies carried out in the NOD mouse [3] where apoptosis was shown to increase with age and to peak immediately before the onset of diabetes. In another study using NOD mice [4], apoptotic cells were detected as early as 3 weeks of age. In contrast with our studies, this early detection of apoptotic beta-cells preceded the appearance of T cells which, the authors speculated, may have triggered beta-cell destruction and diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in agreement with studies carried out in the NOD mouse [3] where apoptosis was shown to increase with age and to peak immediately before the onset of diabetes. In another study using NOD mice [4], apoptotic cells were detected as early as 3 weeks of age. In contrast with our studies, this early detection of apoptotic beta-cells preceded the appearance of T cells which, the authors speculated, may have triggered beta-cell destruction and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental data indicate that apoptosis plays a part in the destruction of beta-cells during onset of Type I diabetes [4,8]. In vitro, apoptosis has been identified as the main mechanism of cell death in islets and beta-cell lines exposed to cytokines and other cellular insults [3,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Programmed cell death, or apoptosis is an important pathogenesis in the development of Type I diabetes [1,2,3]. Morphological changes indicative of apoptosis have been observed in normal islets and appear at an increased frequency in islets with Type I diabetes-associated insulitis [3].…”
mentioning
confidence: 99%
“…Programmed cell death, or apoptosis is an important pathogenesis in the development of Type I diabetes [1,2,3]. Morphological changes indicative of apoptosis have been observed in normal islets and appear at an increased frequency in islets with Type I diabetes-associated insulitis [3]. Defining the signalling components of apoptosis present in beta cells is important because it could provide insights into potential pathogenic mechanisms and might lead to the development of pharmacological interventions for the treatment of Type I diabetes.…”
mentioning
confidence: 99%